The zombie survival guide complete protection from the living dead - Brooks, Max 1972- (Three Rivers Press, 2003)
A guide to surviving an attack by hordes of the predatory undead explains zombie physiology and behavior, the most effective weaponry and defense strategies, how to outfit one's home for a long siege, and how to survive in any terrain
Keywords: Zombies / Humor